Root pull-out resistance and surface microstructural characteristics of adapted plants in the water-level fluctuation zone of the three parallel rivers area - Zhong-liang Wang; Peng-biao Luo; Yuan-jun Yang; Ji-qi Duan; Qing-song Duan (PLoS ONE, 2025)
Root pull-out resistance is an important index to measure the soil-fixing ability of roots. The study aims to investigate the root pull-out resistance and root surface microstructural characteristics of plants adapted to the Water-Level Fluctuation Zone (WLFZ) and provide a reference for the study of vegetation soil reinforcement capacity in the WLFZ of the Three Parallel Rivers area. The study subjects are the four-year-old Arundo donax ‘Versicolor’, Cyperus involucratus, and Acorus calamus. The study employs the single root pull-out resistance experiments to determine their resistance. Additionally, SEM and paraffin sectioning methods were utilized to measure the microstructure of the root surface and to explore the differences in microstructure and their impact on the friction between the root and soil. The findings revealed (1) The failure modes of the single root pull-out experiments included both pull-out and breakage, with 70.83%, 81.48%, and 57.69% of the roots being broken for A. donax ‘Versicolor’, C. involucratus, and A. calamus, respectively. (2)There were significant differences in the average maximum pull-out resistance and average frictional strength among the three plants (P < 0.05), with the average maximum pull-out resistance being A. donax ‘Versicolor’ (27.88 N) > C. involucratus (20.53 N) > A. calamus (13.75 N), and the average frictional strength was A. donax ‘Versicolor’ (43.48 Pa) > C. involucratus (31.77 Pa) > A. calamus (19.05 Pa). The root surface roughness also showed significant differences among the three plants (P < 0.05), with the surface roughness of A. donax ‘Versicolor’ (20.13%) > C. involucratus (16.12%) > A. calamus (9.23%). (3) The root system of A. donax ‘Versicolor’ was relatively rough, with dense depressions and protrusions. In contrast, the root system of A. calamus was relatively smooth with no significant depressions or protrusions, and C. involucratus was intermediate between the two. The results suggested that the maximum pull-out force of single roots for the three plants followed the order of A. donax ‘Versicolor’ > C. involucratus> A. calamus. Moreover, the microstructure of the root surface had a significant impact on the maximum pull-out force of the roots, The rougher the root surface. The greater the single root drawing force.